2022
DOI: 10.1038/s41586-022-04410-z
|View full text |Cite
|
Sign up to set email alerts
|

Early prediction of preeclampsia in pregnancy with cell-free RNA

Abstract: Liquid biopsies that measure circulating cell-free RNA (cfRNA) offer an opportunity to study the development of pregnancy-related complications in a non-invasive manner and to bridge gaps in clinical care1–4. Here we used 404 blood samples from 199 pregnant mothers to identify and validate cfRNA transcriptomic changes that are associated with preeclampsia, a multi-organ syndrome that is the second largest cause of maternal death globally5. We find that changes in cfRNA gene expression between normotensive and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
118
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(145 citation statements)
references
References 52 publications
1
118
0
1
Order By: Relevance
“…Most recently, Moufarrej et al [ 34 ] identified 544 differentially expressed PCF RNAs altered across gestation and postpartum. Focusing on early pregnancy, they identified 18 RNAs differentially expressed in women who developed preeclampsia that based on regression analysis achieved an AUC of 0.99 (CI: 0.99–0.99).…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, Moufarrej et al [ 34 ] identified 544 differentially expressed PCF RNAs altered across gestation and postpartum. Focusing on early pregnancy, they identified 18 RNAs differentially expressed in women who developed preeclampsia that based on regression analysis achieved an AUC of 0.99 (CI: 0.99–0.99).…”
Section: Discussionmentioning
confidence: 99%
“…In Latin America and the Caribbean, hypertensive disorders of pregnancy can be responsible for up to 26% of maternal deaths ( 25 ). It is now mostly believed that preeclampsia occurs in two stages, with placental insufficiency due to intravascular trophoblastic invasion and impaired spiral arterial remodeling in early pregnancy, followed by systemic endothelial dysfunction ( 26 ). Pathological inflammatory changes can cause local immune imbalance, affecting intravascular trophoblastic invasion and spiral artery remodeling, which, in turn, lead to placental dysfunction, representing a risk factor for the development of preeclampsia ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Preeclampsia is a multisystem disorder, characterized by abnormal placentation and maternal vascular dysfunction. Pathologic inflammation in early pregnancy leading to placental dysfunction and the subsequent entry of multiple placental factors into the maternal circulation, causing endothelial damage and clinical signs, are two widely accepted stages in preeclampsia development ( 26 ). Placental development is important for preeclampsia development.…”
Section: Discussionmentioning
confidence: 99%
“…Although a previous study demonstrated that sFlt-1, a well-known blood biomarker for preeclampsia, could predict severe cases of COVID-19 [4, 5], we could not reevaluate the finding in this study, because this biomarker is in a protein form. Instead, we included transcripts from the validated gene set as the fifth method of predictor discovery [30]. Since this gene set was discovered by a differential expression analysis during the COVID-19 pandemic, it is possible that the method falsely discovers blood biomarkers misled by endothelial dysfunction which is a key pathogenic mechanism shared between preeclampsia and COVID-19 infection [16, 17].…”
Section: Methodsmentioning
confidence: 99%